Seasonal changes in performance related characteristics and biochemical marker variability of adolescent table tennis players - Pullinger, S. A.; Varamenti, E.; Nikolovski, Z.; Elgingo, M.; Cardinale, M. (Asian Journal of Sports Medicine, 2019)
Background:There is a shortage of longitudinal surveys in highly trained adolescent table tennis athletes reporting typical changes in performance related, hematological, and biochemical parameters.